2013
DOI: 10.2147/cia.s50333
|View full text |Cite
|
Sign up to set email alerts
|

Decreased functional capacity and muscle strength in elderly women with metabolic syndrome

Abstract: PurposeTo compare the metabolic parameters, flexibility, muscle strength, functional capacity, and lower limb muscle power of elderly women with and without the metabolic syndrome (MetS).MethodsThis cross-sectional study included 28 older women divided into two groups: with the MetS (n = 14; 67.3 ± 5.5 years; 67.5 ± 16.7 kg; 1.45 ± 0.35 m; 28.0 ± 7.6 kg/m2), and without the MetS (n = 14; 68.7 ± 5.3 years; 58.2 ± 9.9 kg; 1.55 ± 0.10 m; 24.3 ± 3.8 kg/m2). Body composition was evaluated by dual-energy X-ray absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 40 publications
1
23
1
Order By: Relevance
“…Metabolic syndrome leads to a pro-inflammatory state and pro-inflammatory cytokine release from adipose tissues may potentiate skeletal muscle catabolism [ 34 ]. An association between metabolic syndrome and lower body muscle strength has been reported in several similar studies investigating adult participants with a wide age range [ 6 8 , 10 ]. In a previously reported case-control study, the univariate analysis indicated that elderly women with metabolic syndrome had reduced relative muscle strength in their lower extremities [ 10 ].…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Metabolic syndrome leads to a pro-inflammatory state and pro-inflammatory cytokine release from adipose tissues may potentiate skeletal muscle catabolism [ 34 ]. An association between metabolic syndrome and lower body muscle strength has been reported in several similar studies investigating adult participants with a wide age range [ 6 8 , 10 ]. In a previously reported case-control study, the univariate analysis indicated that elderly women with metabolic syndrome had reduced relative muscle strength in their lower extremities [ 10 ].…”
Section: Discussionmentioning
confidence: 70%
“…The maximal grip force of the dominant hand was measured to represent upper extremity muscular strength using an analog isometric dynamometer (Baseline hydraulic hand dynamometer, Fabrication Enterprises Inc., Irvington, NY, USA)–the highest value of three attempts was used for analysis [ 17 ]. Lower extremity muscular endurance was evaluated using a sit-to-stand test (participants were asked to stand and sit repeatedly for 30 seconds [with their arms folded across their chests]; the number of repetitions was recorded) [ 10 , 18 ]. The above mentioned equipment and protocol were shown to have good test-retest strength reliability according to a previous study [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Leite Vieira et al [24] have reported in an investigation that elderly women with the metabolic syndrome have higher metabolic risk profile and lower functional capacity, muscle strength, lower limb power, and flexibility as compared to women without the metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…The decline in physical abilities with age often represents the early stage of a process which, associated with sedentarism, institutionalization or comorbidities, leads to dependence and other adverse health outcomes (Vieira et al, 2013).…”
Section: Introductionmentioning
confidence: 99%